1987
DOI: 10.1152/ajpgi.1987.253.4.g452
|View full text |Cite
|
Sign up to set email alerts
|

Interdigestive contractile patterns of the ileum in dogs

Abstract: The aim of this study is to elucidate the nature of ileal interdigestive contractile patterns by the computerized analysis of the contraction spread and by videofluoroscopy. Conscious dogs equipped with closely spaced strain-gauge force transducers were used. Two patterns of repetitive, phasic contractions were recorded, migrating clusters and phase IIIs; both patterns consisted of repetitive, propagated contractions. Both patterns migrated aborad by sequential movement of contraction waves down the bowel. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
1
6
1
1
Order By: Relevance
“…Ohta et al. 17 suggested that the small intestine and colonic motility were somewhat correlated; however, we observed little correlation, as did Siegle and Ehrlein 24 . Our findings indicate that colonic motility plays an important role in the absorption of water and electrolytes and that evacuation is independent of upper gastrointestinal motility.…”
Section: Discussioncontrasting
confidence: 45%
“…Ohta et al. 17 suggested that the small intestine and colonic motility were somewhat correlated; however, we observed little correlation, as did Siegle and Ehrlein 24 . Our findings indicate that colonic motility plays an important role in the absorption of water and electrolytes and that evacuation is independent of upper gastrointestinal motility.…”
Section: Discussioncontrasting
confidence: 45%
“…Siegle, Scheeman, and Ehrlein demonstrated the spatial and temporal characteristics of ileal motility in dogs, using serosal strain‐gauged transducers for extraluminal manometry 5,6 . Basic principles known from duodenojejunal manometry, such as the fasting MMC, postprandially interrupted by an irregular motor response, were confirmed.…”
Section: Introductionmentioning
confidence: 89%
“…What seems more probable is that we were unable to differentiate between phase I11 complexes and other patterns that featured uninterrupted phasic contractions. Such so-called phasic clusters have been described in the distal small intestine in both dog (12,16,22) and human (1 l), their differentiation from phase 111 complexes being possible only by the plac.ement of multiple, closely spaced sensors in the distal small intestine. Failure to differentiate these motor patterns could also account for the apparently shorter duration of phase I1 activity in the catheter rats; clusters, if identified, would contribute to phase I1 activity.…”
Section: Discussionmentioning
confidence: 99%